2022
DOI: 10.55563/clinexprheumatol/8xj0b9
|View full text |Cite
|
Sign up to set email alerts
|

Defining anti-synthetase syndrome: a systematic literature review

Abstract: Anti-synthetase syndrome (ASSD) is a heterogeneous autoimmune disease characterised by multi-system involvement with a wide variety of manifestations. Validated classification criteria are necessary to improve recognition and prevent misclassification, especially given the lack of reliable and standardised autoantibody testing. We systematically reviewed the literature to analyse proposed ASSD criteria, characteristics, and diagnostic performance. PubMed and Embase databases (01/01/1984 to 06/11/2018) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 106 publications
(79 reference statements)
1
5
0
1
Order By: Relevance
“…Antisynthetase syndrome is a heterogeneous disorder that involves different organs and systems. Several diagnostic criteria have been proposed to guide the diagnosis, as it can be challenging [ 6 ]. Connors and Solomon have proposed criteria to facilitate the diagnosis of this rare entity (Table 2 ) [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antisynthetase syndrome is a heterogeneous disorder that involves different organs and systems. Several diagnostic criteria have been proposed to guide the diagnosis, as it can be challenging [ 6 ]. Connors and Solomon have proposed criteria to facilitate the diagnosis of this rare entity (Table 2 ) [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review revealed numerous variabilities in defining ASyS across the literature, coupled with a lack of sensitivity and specificity of its clinical variables including muscle biopsy findings. 130 In our practice, we have a high index of suspicion for ASyS even in the absence of extrapulmonary symptoms, especially in patients with an NSIP, OP, or NSIP-OP overlap pattern of ILD; and routinely screen for ASA. Despite the above-mentioned limitations, we rely on Connor's criteria because of our long-standing experience with it and its relative simplicity.…”
Section: Diagnosismentioning
confidence: 99%
“…Presently, no data driven or validated classification criteria exist for ASyS and definitions vary widely across the literature and are poorly evidenced ( 11 ). Project CLASS is an ongoing large multicentre international effort funded by EULAR and ACR aiming to develop a validated criteria set for ASyS.…”
Section: Classification and Epidemiologymentioning
confidence: 99%